2012
DOI: 10.1007/s10120-012-0195-9
|View full text |Cite
|
Sign up to set email alerts
|

The Cholegas Study: safety of prophylactic cholecystectomy during gastrectomy for cancer: preliminary results of a multicentric randomized clinical trial

Abstract: Background Cholelithiasis is more frequent in patients after gastrectomy, due to dissection of vagal branches and gastrointestinal reconstruction. Methods A randomized controlled trial was conducted from November 2008 to March 2012. Patients were randomized into two groups: prophylactic cholecystectomy (PC) and standard gastric surgery only (SS) for curable cancers. We planned three end points: evaluation of the number of patients who developed symptoms and needed further surgery for cholelithiasis after stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 28 publications
(42 reference statements)
2
38
0
1
Order By: Relevance
“…However, one case (1.5%) of biliary leakage that was probably caused by prophylactic cholecystectomy was observed [10]. Another Japanese study concluded that the addition of laparoscopic cholecystectomy did not alter complications, mortality, and length of stay in patients undergoing laparoscopic gastrectomy for gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one case (1.5%) of biliary leakage that was probably caused by prophylactic cholecystectomy was observed [10]. Another Japanese study concluded that the addition of laparoscopic cholecystectomy did not alter complications, mortality, and length of stay in patients undergoing laparoscopic gastrectomy for gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This approach also avoided the possibility of subsequent cholecystectomy, which might be difficult owing to potential adhesion at the upper abdomen caused by previous gastrectomy and lymph node dissection [9]. A multicenter, randomized controlled trial, the Cholegas study, was initiated in November 2008 to evaluate prophylactic cholecystectomy; however, the final result has not been disclosed yet [10].…”
Section: Introductionmentioning
confidence: 99%
“…Combined cholecystectomy for asymptomatic gallstone in GC surgery may be considered in young patients; otherwise, it is not clear if cholecystectomy is indicated in patients without gallstones; a recent GIRCG multicenter study showed no difference in medium-term outcome between patients receiving or not receiving prophylactic cholecystectomy [18].…”
Section: Surgical Therapy Resectionmentioning
confidence: 99%
“…Preliminary results of a multicentric randomized clinical trial'' [1]. His interest in this work is highly appreciated.…”
mentioning
confidence: 99%